Semiotika Nonverbal dalam Musik Video “Azza” Karya Rhoma Irama (Kajian Semiotika Roland Barthes) - Anindita Fikri Amalia; Nurdien Harry Kristanto; Sukarjo Waluyo (Universitas Mulawarman, 2022)
This study aims to describe non-verbal semiotics and its relation to Roland Barthes' semiotics, namely connotation and denotation. This research with the object of the study of the music video